Gumuk gunung api purba bawah laut di Tawangsari - Jomboran, Sukoharjo - Wonogiri, Jawa Tengah - Hartono, Gendoet; Sudrajat, Adjat; Syafri, Ildrem (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no1.20084This paper discusses the study on the basalt volcanic rocks and the volcano morphology indicating the existence of an ancient submarine volcano in Tawangsari-Jomboran sub-regency, Sukoharjo- Wonogiri, Central Java. In general, this basalt volcanic rocks were identified as andesite breccia which might be grouped into the Mandalika Formation of Oligosen-Miosen age (Surono et al., 1992). The origin of the Mandalika Formation in relation to the classic sedimentation process and the submarine volcanism is still needed to be evaluated. The present study was based on the detailed descriptions of the rocks both in the field and in the laboratory. The autoclastic basalt outcrops consisting of breccias show the characteristics of the igneous rock fragment component embedded in the groundmass with the same composition, namely igneous rock, dark grey to black in colour; porphyritic texture, rough surface, brecciated; pillow structures, massive, fine vesicularities, amygdaloidal filled with calcite, and radial fractures; calk-alkaline andesite composition ( SiO = 54.71% , K O = 1.15% ). This rock body attains the  dimension of 2 - 5 m length, and 40 cm - 1 m in diameter with the direction of the deposition varies following the direction of the eruption source. Brecciated structures on the surface was controlled by the high cooling rate and the low flow, while the interior of the rock is massive because it was not in a direct contact to the cooler mass outside. Autoclastic basalt breccias and or the pillow basalt lava was interpreted to be formed by the undulating low gradient of morphology with the average angle of <10o. On the other hand, the low basaltic magma viscosity produced the effusive eruption related to the formation of the low angle morphology. The distance between the hills generally composed of pillow basalt is between 500 m - 1 km. The typical pillow structure of the igneous rock as described above is interpreted to be the product of the lava flow related to the effusive eruption  from a submarine volcano located under or close to the seawater surface.